High mechanical and thermal performance of Sasobit-modified epoxy resin, prepared via vacuum shock technique. (January 2020) - Jahandideh, Sara; Sarraf Shirazi, Mohammad Javad; Tavakoli, Mitra; Mousavi, Seyyed Mojtaba; Hashemi, Seyyed Alireza
Abstract: In this study, thermal and mechanical properties of novel nanocomposite, epoxy resin reinforced with octadecylamine functionalized graphene oxide (GO-ODA) and Sasobit, prepared via creative vacuum shock technique, were investigated. By introducing 1, 3 and 5 wt% Sasobit to the neat epoxy resin, the tensile strength increased remarkably by 104%, 315% and 266%, respectively due to the unique stiff and crystalline structure of Sasobit. In addition, considerable enhancement of 125% in Young's modulus, 351% in toughness, 562% in impact resistance, 19 °C in thermal stability and 7 °C in glass transition temperature of epoxy resin with 3 wt% Sasobit loading was demonstrated. The composite containing 3 wt% Sasobit alone, were found to have even superior properties than GO-ODA/epoxy nanocomposite, as surprisingly 3, 2.9, 2.2 and 2 times more improvement, respectively in tensile strength, toughness, impact strength and thermal stability of epoxy resin compared to reinforcement with GO-ODA were obtained. Highlights: Epoxy-based composites were reinforced with Sasobit and octadecylamine functionalized graphene oxide (GO-ODA). Vacuum shock technique was employed for development of defect less composites. Sasobit considerably increased the tensile strength, toughness, impact strength and thermal stability of epoxy resin. The composite containing 3 wt% Sasobit showed superior properties over GO-ODA/epoxy nanocomposite. Sasobit proved to be an ideal economic candidate instead of graphene by-products for reinforcement/modification of nanocomposites.